2019
DOI: 10.1177/1748048518825322
|View full text |Cite
|
Sign up to set email alerts
|

Editorial boards in communication sciences journals: Plurality or standardization?

Abstract: This research-based essay examines the national diversity of editorial boards from a selection of journals in communication sciences. Specifically, it reviews the board composition of 39 Journal Citation Report journals indexed in quartile one (Q1) and quartile two (Q2) in the category of ‘communication’, proposing a typology of dominant nationalities. The most distinguished countries are the United States, United Kingdom, Canada, Australia and Germany, monopolizing 79.4% of total members. The exaggerated domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 47 publications
1
37
0
4
Order By: Relevance
“…Finally, our findings revealed that more recently founded journals are more sensitive to geographical inclusion in terms of data collection, playing a statistically significant role as moderators in the relationship between EB diversity and the diversity of first author origin and research approach. This study contributes to a growing body of scholarship on how EBs affect what is published (Goyanes, 2019) and research inequalities between Global North/South regions in communication studies.…”
mentioning
confidence: 94%
“…Finally, our findings revealed that more recently founded journals are more sensitive to geographical inclusion in terms of data collection, playing a statistically significant role as moderators in the relationship between EB diversity and the diversity of first author origin and research approach. This study contributes to a growing body of scholarship on how EBs affect what is published (Goyanes, 2019) and research inequalities between Global North/South regions in communication studies.…”
mentioning
confidence: 94%
“…Con el objetivo de responder a las preguntas de investigación planteadas se diseñó un análisis de contenido, estructurado en siete pasos: 1) establecimiento de las se asume que las revistas con un mayor factor de impacto son más relevantes. Además, y tal vez más importante, este ranking se utiliza cada vez más como fuente de referencia para los ejercicios de evaluación (Goyanes, 2019) y, en consecuencia, las instituciones académicas tienden a incentivar a sus académicos a publicar sus investigaciones en esas revistas. En este sentido, muchos países han adoptado formal e informalmente el ranking JCR para disciplinar y recompensar a sus académicos e instituciones.…”
Section: Materials Y Métodosunclassified
“…Concretamente, los resultados muestran una exagerada dominación de determinadas zonas geográficas (especialmente Estados Unidos) y de los hombres. Los hallazgos se encajan, sin embargo, dentro de un contexto socio-científico en el que la heterogeneidad y pluralidad, se constituyen como valores clave del progreso social y científico (Goyanes, 2019;Alvesson, Gabriel y Paulsen, 2017). El estudio demuestra cómo la intersección entre el poder y el conocimiento está dominado por un puñado de países y perfiles académicos.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Language can be used as a proxy for broader ways of knowing. 34,35 The insistence on English as the language of science can exacerbate existing unequal power relationships 36,37 and dominant epistemic cultures 38 by reinforcing cultural imperialism. 39 Such concerns have led to calls for scientists to develop mechanisms to overcome language barriers and be more inclusive of non-English-language literature, regardless of discipline.…”
Section: Introductionmentioning
confidence: 99%